Analisis Tingkat Kepuasan Mahasiswa FISIP USU terhadap Penggunaan QRIS Pada UKM di Sekitar USU - Mahdiya, Shakila Aulia; Rossevelt, Franklin Asido; Aisyah, Dara; Siregar, Theresia Rani Miranda; Hutabarat, Sepania Margareta; Siringoringo, Lody Chrisandi Irwanto; Silaen, Priskila Eunike Avelia (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study aims to assess the extent to which the use of the Indonesian Standard Quick Response Code (QRIS) affects the satisfaction of FISIP University of North Sumatra students in conducting transactions at SMEs around the campus. The method used is a descriptive-associative quantitative approach with data collection through questionnaires, observation, and documentation. A total of 30 respondents were selected using purposive sampling. All instruments were declared valid and reliable based on the results of the tests conducted. The analysis showed a very strong relationship between the use of QRIS and student satisfaction, with a correlation coefficient of 0.888 and an R Square value of 0.788. A simple linear regression test also proved that the use of QRIS had a significant effect on student satisfaction (p < 0.001). These results confirm that the factors of convenience, speed, security, and comfort offered by QRIS significantly increase student satisfaction in transactions at SMEs around USU.